The influence of photographs as a visual stimuli on traditional knowledge of two medicinal tree species - Coêlho, Maria Naianny Rodrigues; Baptistel, Andrea Cristiane; Sousa Jr., José Ribamar; Marcelino Monteiro, Júlio (Scientia Plena, 2020)
This study aimed to verify the efficiency of photographs as visual stimuli and the knowledge of the Santo Antonio community, Piauí, Northeast Brazil, on two species widely used in local therapy. Semi-structured interviews were conducted using the checklist/inventory method which consisted in offering clear pictures to informants. Furthermore, local knowledge was also analyzed using quantitative measurements. The present study cited 16 uses for amburana (A. cearenses) and ten uses for mangabeira (L. replicata); moreover, the use of visual stimuli proved to be inefficient with respect to the recognition of these two tree species (A. cearenses and L. replicata) in the studied community. The results obtained, despite the knowledge of only two species, can add to the information provided about the specific domain of knowledge regarding the medicinal plants, because the selected species are very popular in the region.